Nilai-Nilai Budaya Dalam Cerita Rakyat Baturaden Pada Masyarakat Banyumas Sebagai Alternatif Bahan Ajar Sastra Di Sekolah Dasar - Cut Alfina Umri (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The problem in this study is the decline in the application of cultural values to elementary school students. This study aims to analyze the cultural values contained in the Baturaden folklore in the Banyumas community which will be used as alternative materials for teaching oral literature at the elementary school level. The research method applied in this research is content analysis method. Data collection techniques were carried out by interview, observation and documentation. The results of interviews and observations show that there are various versions of the Baturaden folklore. In addition, the intrinsic elements in Baturaden folklore also vary. This happened because the data were taken from Banyumas people from various regions, age differences, and different professions. The cultural values contained in the Baturaden folklore are the nature of the human relationship with God, the nature of the human relationship with nature, the nature of human relations with each other, and the nature of the human relationship with oneself. Based on the cultural values and intrinsic elements contained in the Baturaden folklore, it can be used as an alternative literature for teaching materials in elementary schools so that students can apply it in their daily lives.